The Effect of Locus of Control, Framing, Pressure of Obedience and Auditor's Competency on Audit Judgment - Awaluddin La Dana; Hadi Sunaryo; Supriyanto Supriyanto (Budapest International Research and Critics University, 2022)
This study aims to investigate in depth the effect of locus of control, framing, obedience pressure and auditor competence on audit judgment either partially or simultaneously. This research was conducted at 7 Public Accounting Firms in Malang City with the respondents' criteria, namely auditors who have worked for more than one year and obtained a sample of 57 respondents. Collecting data using a questionnaire that has been distributed manually using a questionnaire that has been validated. The results of data collection were then analyzed using multiple linear regression using the SPSS version 25 program. The results showed that simultaneously the locus of control, framing, obedience pressure and auditor competence variables had a significant effect on audit judgment. Then partially locus of control, framing and auditor competence variables have a significant effect on audit judgment. Surprisingly, the obedience pressure variable has no significant effect on audit judgment. So, it still needs to be discussed further.